Bollywood and Fashion Trends in India: A Longitudinal Study - Kanupriya Gupta, Jashandeep Singh, (International Journal of Scientific Research and Management (IJSRM), 2014)
India has very rich and varied textile heritage. The languages and dialects, foods and culture change every 80-100 kilometers. Each region of India is having a very unique traditional costumes and accessories. Therefore, every region has a different view of fashion which makes its fashion as diverse as the culture and traditions of the country. The fashion in India is not only confined within the limits of the country but a perfect touch of western culture can also be witnessed in the developed and some underdeveloped cities of the country; and all this has been done by Indian Film Industry-“Bollywood” only. This purpose of this paper is to throw some light over the impact of Bollywood on fashion in India.